The Role of Social Networks in the Evolution of Al Qaeda-inspired Violent Extremism in the United States, 1990-2014 - Klausen, Jytte ([Verlag nicht ermittelbar], 2021)
This study compiled data on American jihadists and other Islamic extremists recruited since the early 1990s. Specifically, "homegrown" terrorist, referring to Americans and other Westerners who are inspired to commit acts of terrorism or support those committing these acts in their home country on behalf of foreign terrorist organizations, are the main focus. The purpose of this research is to address the central question: How do foreign terrorist organizations mobilize Americans to carry out attacks on their behalf? Variables collected include extremist group affiliation, criminal background, foreign fighter history if applicable, coconspirators and their relationship, and the location and nature of terrorist plots. Demographic variables include sex, ethnicity, immigration status, education, and profession.